The Spectrum of Psychiatric Pathology in a Patient with Genetically Verified Huntington’s Disease - Alkabie, Samir; Singh, Daljinder; Hernandez, Amy; Dumenigo, Rhaisa (Case Reports in Psychiatry, 2015)
Psychiatric and behavioral disturbances are common in Huntington’s disease (HD) and contribute significantly to its morbidity and mortality. We herein present the case of a 43-year-old woman with genetically verified HD, whose deteriorating psychiatric condition necessitated multiple inpatient psychiatric hospitalizations and featured a clinical spectrum of neuropsychiatric disturbances classically associated with HD. This paper reviews the literature concerning Huntington’s psychopathology and provides an illustrative case example of its clinical nature.